THE INFLUENCE OF THE REALISTIC MATHEMATICS EDUCATION LEARNING APPROACH ON THE CRITICAL THINGKING SKILLS OF FIFTH GRADE ELEMENTERY SCHOOL STUDENTS IN MATHEMATICS LEARNING - HIDAMAN YUSUF HIDAMAN; Sunardi; Tri Dyah Prastiti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Realistic Mathematics Education approach is able to make students more active, creative, think, and brave in expressing their opinions and are able to create more creative and enjoyable mathematics learning conditions. The purpose of this study was to determine the effect of the realistic mathematics education learning approach on the critical thinking skills of fifth grade elementary school students in mathematics learning. The research design used was experimental research. The population used fifth grade students of SDN 1 Blimbingsari and SDN 2 Blimbingsari. The sampling technique used was simple random sampling. The instruments used were pretest and posttest questions. The normality test was carried out using the Shapiro-Wilk statistical test, the results obtained showed that the data was normally distributed (> 0.05). Based on the results of the homogeneity test, homogeneous results were obtained. Based on the results of the independent sample test, the Sig. (2-tailed) results were obtained of 0.000 <0.05, it can be concluded that there is a significant effect of the learning approach using RME on the critical thinking skills of fifth grade elementary school students in learning mathematics volume of solid shapes.